The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.48550/arxiv.2112.14668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gravitational dark matter: free streaming and phase space distribution

Abstract: Gravitational dark matter (DM) is the simplest possible scenario that has recently gained interest in the early universe cosmology. In this scenario, DM is assumed to be produced from the decaying inflaton through the gravitational interaction during reheating. Gravitational production from the radiation bath will be ignored as our analysis shows it to be suppressed for a wide range of reheating temperature (T re ).Ignoring any other internal parameters except the DM mass (m Y ) and spin, a particular inflatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…On the perturbative side, gravitational production of dark matter with a graviton mediator has been studied in [26-28, 113, 114], where it was shown that such processes play a dominant role during reheating. Similar processes involving the inflaton condensate scattering to thermal bath particles were studied in [27,115]. However, we argue here that such a simple perturbative picture of gravitational production of dark matter is insufficient since it does not account for the tachyonic growth of the superhorizon modes.…”
Section: Comparison With Previous Workmentioning
confidence: 66%
“…On the perturbative side, gravitational production of dark matter with a graviton mediator has been studied in [26-28, 113, 114], where it was shown that such processes play a dominant role during reheating. Similar processes involving the inflaton condensate scattering to thermal bath particles were studied in [27,115]. However, we argue here that such a simple perturbative picture of gravitational production of dark matter is insufficient since it does not account for the tachyonic growth of the superhorizon modes.…”
Section: Comparison With Previous Workmentioning
confidence: 66%
“…Our conclusion so far seems to be independent of any new physics in the visible sector. However, if one introduces explicit coupling (say β) between DM and radiation bath, the DM masses obtained in our analysis become the maximum possible value m max Y in (β, m Y ) space, above which the universe will be over-abundant (see detail discussion in [2]). Therefore, an important conclusion we can arrive at is that detection of DM with m Y > m max Y will automatically rule out the possibility of purely gravitational reheating, at least in the framework of de-Sitter inflation.…”
mentioning
confidence: 86%
“…Therefore, peak appears for fermionic PDFs at m φ (t) = m Y . However, this distinguishing feature happens only for ω φ > 5/9 (see [2] for detailed discussions) Conclusions: GRe phenomena appeared to be a unique scenario through which our present state of the universe can be obtained after inflation. Because of DM mass being a only free parameter during this phase, realizing such scenario put stringent constraint on the possible models of inflation and DM mass.…”
mentioning
confidence: 91%
See 2 more Smart Citations